A 3D magnetohydrodynamic simulation of the propagation of a plasma plume transverse to applied magnetic field. (13th October 2021) - Patel, Bhavesh G; Behera, Narayan; Singh, R K; Kumar, Ajai; Das, Amita
Abstract: We have carried out a 3D ideal-MHD (magnetohydrodynamic) simulation to study the evolution of a laser-generated plasma plume in a moderate external magnetic field (0.13 T) oriented perpendicular to the flow direction of the plasma plume. The simulation shows that the plasma plume pushes the external magnetic field lines outward in the direction of the expansion. This leads to the compression and bending of the magnetic field lines. The force resulting from the change in shape and the density of the magnetic field lines opposes the expansion of the plume. An elliptic layer of shocked plasma is formed at the plasma/external field interface leaving a cavity in the plume core due to the outward expansion and the inertia of the plume. As the plasma pressure drops due to expansion, the imbalance between the magnetic energy and the internal energy results in the collapse of the cavity. These observations have striking similarities with the observations of the experiments (Behera et al 2017 Phys. Plasmas 24 033511) performed recently to study the plasma plume expansion in the presence of an external transverse magnetic field. This similarity indicates that the physical mechanisms dominantly governing the plasma plume expansion in the moderate magnetic field are aptly described in the ideal MHD regime. The studies thus show that the laser-generated plasma plume can be utilized to carry out interesting experiments on MHD phenomena in a simple laboratory setup.